Effects of gamma irradiation in the antimicrobial activity of wild mushroom extracts - Fernandes, Ângela (2015)
The interest of mushrooms has been increasing over time due to their potential in prevention or treatment of different diseases. Mushrooms have been reported for their anticancer, anti-inflammatory, and immunosuppressive and antimicrobial properties. In particular, several authors reported the antibacterial activity of extracts prepared from different mushroom species [1]. In spite of these undeniable qualities, mushrooms are one of the most perishable products and tend to loose quality immediately after harvest. Irradiation is recognized as a safe and effective preservation method, being used worldwide to increase the shelf life of foods (e.g., fruits and vegetables, spices, grains, meat or seafood, aromatic and medicinal plants and spices) [2, 3]. In the present study, the antibacterial properties of methanolic extracts prepared from Boletus edulis Bull. and Hydnum repandum L. Fr., previously submitted to gamma irradiation, were assessed against clinical isolates with different resistance profiles (two Gram negative bacteria: Escherichia coli and Proteus mirabilis, isolated from urine, and two Gram positive bacteria: MSSAmethicillin- sensitive Staphylococcus aureus, isolated from wound exudate and MRSA- methicillin-resistant Staphylococcus aureus, isolated from expectoration) from hospitalized patients in Local Health Unit of Mirandela, Northeast of Portugal. The fruiting bodies were collected in Trás-os-Montes (Northeast of Portugal) in November 2012. Gamma irradiation was performed in experimental equipment with four 60Co sources at 1 and 2 kGy doses